It takes a village: Guarding against sexual abuse in Australian educational settings - Robertson, Amanda Lee (Journal of criminology, 2024)
Reporting indicators of child sexual abuse is critical to intervention and prevention. However, guardianship and its mechanisms in educational settings have been empirically neglected. We address this gap by analysing a unique administrative dataset from an Australian jurisdiction that captures alleged improper sexual conduct by school employees against adolescents aged 13–17 years inclusive. We analysed 638 cases reported to an external oversight body in accordance with the New South Wales “reportable conduct” scheme between 2015 and 2019. These cases detailed information about the sources of allegations, including how allegations arose and who brought them forward. Results established school personnel and families as the key reporters and supported young people's potential as capable guardians. Guardianship was highly context-dependent and differed according to event, victim, and perpetrator characteristics. Recommendations for strengthening guardianship in schools are presented, including enabling reporting pathways for students, building contextual awareness through policy dissemination and training, and heeding indirect sources of information like rumours.